What is Gnosticism? - King, Karen L., 1954- (Cambridge, Mass. : Belknap Press of Harvard University Press, 2003)
A study of gnosticism examines the various ways early Christians strove to define themselves in a pluralistic Roman society, while questioning the traditional ideas of heresy and orthodoxy that have previously influenced historians
Why is gnosticism so hard to define? -- Gnosticism as heresy -- Adolf von Harnack and the essence of Christianity -- History of religions school -- Gnosticism reconsidered -- After Nag Hammadi I, categories and origins -- After Nag Hammadi II, typology -- End of gnosticism?
Includes bibliographical references (pages 249-275) and index
Keywords: Harnack, Adolf von, -- 1851-1930; Nag Hammadi codices; Gnosticism